IgA Anticardiolipin Antibodies – Relation with other Antiphospholipid Antibodies and Clinical Significance - Selva-O’Callaghan, Albert; Ordi-Ros, Josep; Monegal-Ferran, Francesc; Martinez, Nuria; Cortes-Hernandez, Fina; Vilardell-Tarres, Miquel (Thrombosis and Haemostasis, 1998)
Objective: To evaluate the usefulness of IgA antiphospholipid antibodies as markers of thrombosis and/or antiphospholipid antibody syndrome. Patients and Methods: A cross-sectional study design in a tertiary, university-based, autoimmune reference hospital. Seven-hundred ninety-five patients classified into five different groups – autoimmune diseases (255), deep vein thrombosis (153), transitory ischemic attacks (108), obstetric complications (196), infectious diseases (83) and controls (81) – were tested for IgA, IgG and IgM aPL, and lupus anticoagulant. Plasma and serum samples were drawn for detection of aPL using an internationally standardized ELISA method and LA was carried out using coagulometric assays. Results: True IgA aPL were found only in two patients with systemic lupus erythematosus; these patients were also positive to IgG aPL. Conclusion: The incidence of true positivity to IgA anticardiolipin antibodies is extremely low. Their determination was not helpful in diagnosing the antiphospholipid syndrome or in explaining thrombotic events or aPL related manifestations – fetal loss – in the groups studied.